Rutile high-entropy metal oxynitride catalysts, methods of making and using the same

CN122959780APending Publication Date: 2026-10-23THE HONG KONG POLYTECHNIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510470003.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-15
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]本申请的目的在于提供一种金红石型高熵金属氮氧化物催化剂及其制备方法和应用,旨在解决现有的ENRR中的催化剂的性能普遍较低,且成本还高,导致无法很好的满足商业化生产和应用的问题

Benefits of technology

[0025]本申请第一方面提供的金红石型高熵金属氮氧化物催化剂中,具有较多的氧空位(VO)和氮空位(VN),进而应用于电催化合成氨中,有利于氮气的吸附的同时,还提供了额外活性位点;并且,五种过渡金属元素呈高度混合熵状态,各金属之间具有协同作用,并因各金属原子尺寸差异引发了晶格畸变效应,暴露出更多活性位点,有利于氮气的活化,使得该催化剂在电催化氮气还原合成氨气反应中表现出不凡的催化效果,催化效率高,有利于工业化生产和应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122959780A_ABST
    Figure CN122959780A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of electrocatalytic synthesis of ammonia, in particular to a rutile type high-entropy metal oxynitride catalyst and a preparation method and application thereof. The rutile type high-entropy metal oxynitride catalyst comprises Fe elements, Co elements, Ti elements, V elements, Sn elements, O elements and N elements. The rutile type high-entropy metal oxynitride catalyst has more oxygen vacancies and nitrogen vacancies, is applied to electrocatalytic synthesis of ammonia, is beneficial to adsorption of nitrogen, the five transition metal elements are in a high mixed entropy state, the metals have a synergistic effect, nitrogen activation is facilitated, and the catalyst has high catalytic efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of electrocatalytic ammonia synthesis technology, and particularly relates to a rutile-type high-entropy metal nitrogen oxide catalyst, its preparation method and application. Background Technology

[0002] Ammonia (NH3) plays an important role in global industrial and agricultural production. Currently, the main method for industrial synthesis of NH3 is the Haber-Bosch process, which typically requires high temperature and pressure, resulting in high energy consumption and carbon dioxide (CO2) emissions.

[0003] As a result, the electrocatalytic nitrogen reduction reaction (ENRR) for green synthesis of NH3 has received increasing attention and research due to its significant energy efficiency advantages and environmental friendliness.

[0004] The selection and design of catalysts are crucial in ENRR (Enhanced Energetic Reactor) applications. However, existing ENRR catalysts generally have low performance and high cost, making them unsuitable for commercial production and applications. Summary of the Invention

[0005] The purpose of this application is to provide a rutile-type high-entropy metal nitrogen oxide catalyst, its preparation method and application, in order to solve the problem that the existing catalysts in ENRR generally have low performance and high cost, which makes it difficult to meet the needs of commercial production and application.

[0006] To achieve the above-mentioned objectives, the technical solution adopted in this application is as follows:

[0007] In a first aspect, this application provides a rutile-type high-entropy metal nitride catalyst, wherein the rutile-type high-entropy metal nitride catalyst comprises Fe, Co, Ti, V, Sn, O, and N elements, and the rutile-type high-entropy metal nitride catalyst has multiple oxygen vacancies and multiple nitrogen vacancies.

[0008] In some embodiments, the average particle size of the rutile high-entropy metal oxide catalyst is 8.44 nm to 8.82 nm.

[0009] In some embodiments, the rutile high-entropy metal nitride catalyst has an atomic weight ratio of Fe, Co, Ti, V, Sn, O, and N of 4.56:3.90:8.67:7.92:8.26:60.63:6.06 based on a total atomic weight of 100 at.%.

[0010] In some embodiments, the rutile-type high-entropy metal oxide catalyst has a single-phase rutile crystal structure.

[0011] Secondly, this application provides an electrocatalytic ammonia synthesis apparatus, comprising the aforementioned rutile-type high-entropy metal nitrogen oxide catalyst.

[0012] Thirdly, this application provides a method for preparing a rutile-type high-entropy metal oxide catalyst, comprising the following steps:

[0013] It forms rutile-type high-entropy metal oxides containing Fe, Co, Ti, V, Sn, and O elements;

[0014] The rutile-type high-entropy metal oxide is subjected to plasma nitriding treatment to form the rutile-type high-entropy metal nitride catalyst; wherein the rutile-type high-entropy metal nitride catalyst further includes nitrogen element, and the rutile-type high-entropy metal nitride catalyst has multiple oxygen vacancies and multiple nitrogen vacancies.

[0015] In some embodiments, the formation of the rutile-type high-entropy metal oxide containing iron, cobalt, titanium, vanadium, tin, and oxygen comprises:

[0016] SnCl2, CoCl2·6H2O, FeCl3·6H2O, Ti(OC4H9)4 and NH4VO3 were all dispersed in a solvent at the same molar mass to form a solution;

[0017] An alkaline solution is added to the solution and the pH is adjusted to neutral. The solution is then allowed to stand at a first temperature to obtain a solid powder. The first temperature is 180°C to 250°C.

[0018] The solid powder is calcined at a second temperature and then cooled to form the rutile-type high-entropy metal nitride catalyst; wherein the second temperature is 550℃~650℃.

[0019] In some embodiments, the step of adding an alkaline solution to the solution and adjusting the pH to neutral, followed by standing at a first temperature to obtain a solid powder includes:

[0020] Add 2 mL to 6 mL of a 0.5 M to 1 M sodium hydroxide solution to the solution to adjust the pH to neutral. Then transfer the solution to a high-pressure reactor and let it stand at 180 °C to 250 °C for 10 h to 14 h. After washing with ethanol and water in sequence, dry the solution to obtain the solid powder.

[0021] In some embodiments, calcining the solid powder at a second temperature and then cooling it to form the rutile-type high-entropy metal oxide catalyst includes:

[0022] The solid powder is placed in an air atmosphere in a tube furnace and calcined at 550℃~650℃ for 1h~4h, then naturally cooled to room temperature to form the rutile-type high-entropy metal nitride catalyst.

[0023] In some embodiments, the step of plasma nitriding the rutile-type high-entropy metal oxide to form the rutile-type high-entropy metal nitride catalyst includes:

[0024] The rutile high-entropy metal oxide is placed in the cavity of a nitrogen-rich discharge plasma device, and nitrided for 1 to 4 hours by applying a voltage of 45 kV to 70 kV to form the rutile high-entropy metal oxide catalyst.

[0025] The rutile high-entropy metal oxide catalyst provided in the first aspect of this application has a relatively large number of oxygen vacancies (V0). O ) and nitrogen vacancy (V N This catalyst, when applied to the electrocatalytic synthesis of ammonia, not only facilitates nitrogen adsorption but also provides additional active sites. Furthermore, the five transition metal elements are in a highly mixed entropy state, exhibiting synergistic effects among the metals. The differences in atomic size among the metals trigger a lattice distortion effect, exposing more active sites and facilitating nitrogen activation. As a result, this catalyst demonstrates remarkable catalytic performance in the electrocatalytic reduction of nitrogen to ammonia, exhibiting high catalytic efficiency and being beneficial for industrial production and application.

[0026] The electrocatalytic ammonia synthesis device provided in the second aspect of this application uses a rutile-type high-entropy metal nitrogen oxide catalyst with high catalytic efficiency. This catalyst exhibits excellent selectivity for ammonia synthesis in ENRR, thus having a high Faraday efficiency. As a result, the ammonia synthesized by the electrocatalytic ammonia synthesis device is highly efficient, which is beneficial for industrial production and application.

[0027] The method for preparing rutile-type high-entropy metal oxide catalysts provided in the third aspect of this application firstly prepares rutile-type high-entropy metal oxides containing five transition metal elements: Fe, Co, Ti, V, and Sn, using a hydrothermal method. Then, the prepared rutile-type high-entropy metal oxides are processed by a plasma nitriding process to obtain rutile-type high-entropy metal oxide catalysts with multiple active sites. The raw materials for the preparation of this catalyst are abundant and inexpensive, thus exhibiting high cost-effectiveness. Furthermore, the preparation method is simple and novel, conforms to the principles of green chemistry, and is conducive to industrial production and application. Attached Figure Description

[0028] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0029] Figure 1 A process flow diagram for preparing a rutile-type high-entropy metal nitrogen oxide catalyst provided in this application embodiment;

[0030] Figure 2 A process flow diagram for preparing another rutile-type high-entropy metal nitrogen oxide catalyst provided in this application embodiment;

[0031] Figure 3 A process flow diagram for preparing another rutile-type high-entropy metal nitrogen oxide catalyst provided in the embodiments of this application;

[0032] Figure 4 A process flow diagram for preparing another rutile high-entropy metal nitrogen oxide catalyst provided in the embodiments of this application;

[0033] Figure 5 XRD patterns of FeCoTiVSnON and TiON provided in the embodiments of this application;

[0034] Figure 6 SEM images of FeCoTiVSnON provided in the embodiments of this application;

[0035] Figure 7 STEM image of FeCoTiVSnON provided in the embodiments of this application;

[0036] Figure 8 STEM image of TiON provided in the embodiments of this application;

[0037] Figure 9 XPS spectra of FeCoTiVSnON and FeCoTiVSnO provided for embodiments of this application;

[0038] Figure 10 XPS spectra of Fe in FeCoTiVSnON and FeCoTiVSnO provided in the embodiments of this application;

[0039] Figure 11 XPS spectra of Co in FeCoTiVSnON and FeCoTiVSnO provided for embodiments of this application;

[0040] Figure 12XPS spectra of Ti in FeCoTiVSnON and FeCoTiVSnO provided for embodiments of this application;

[0041] Figure 13 XPS spectra of V in FeCoTiVSnON and FeCoTiVSnO provided for embodiments of this application;

[0042] Figure 14 XPS spectra of Sn in FeCoTiVSnON and FeCoTiVSnO provided for embodiments of this application;

[0043] Figure 15 XPS spectra of O in FeCoTiVSnON and FeCoTiVSnO provided for embodiments of this application;

[0044] Figure 16 XPS spectra of N in FeCoTiVSnON and FeCoTiVSnO provided for embodiments of this application;

[0045] Figure 17 EPR spectra of FeCoTiVSnON and FeCoTiVSnO provided in the embodiments of this application;

[0046] Figure 18 EPR spectra of FeCoTiVSnON and TiON provided for embodiments of this application;

[0047] Figure 19 Ammonia production rate and Faraday efficiency of FeCoTiVSnON in the electrocatalytic reduction of nitrogen to ammonia in the optimal potential range provided in the embodiments of this application;

[0048] Figure 20 A diagram showing the ammonia production rate and Faraday efficiency of TiON electrocatalytic nitrogen reduction to ammonia in the optimal potential range provided in the embodiments of this application;

[0049] Figure 21 The diagram shows the cycling stability of FeCoTiVSnON at the optimal potential, as provided in the embodiments of this application. Detailed Implementation

[0050] To make the technical problems, technical solutions, and beneficial effects of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0051] In this application, the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.

[0052] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0053] It should be understood that in the various embodiments of this application, the order of the above processes does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.

[0054] The terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application. The singular forms "a" and "the" as used in the embodiments of this application and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.

[0055] The weights of the relevant components mentioned in the embodiments of this application can refer not only to the specific content of each component, but also to the proportional relationship between the weights of the components. Therefore, any scaling up or down of the content of the relevant components according to the embodiments of this application is within the scope disclosed in the embodiments of this application. Specifically, the mass described in the embodiments of this application can be a mass unit known in the chemical industry, such as μg, mg, g, or kg.

[0056] The terms "first" and "second" are used for descriptive purposes only, to distinguish objects, such as substances, from one another, and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. For example, without departing from the scope of the embodiments of this application, "first XX" may also be referred to as "second XX," and similarly, "second XX" may also be referred to as "first XX." Thus, features defined with "first" and "second" may explicitly or implicitly include one or more of that feature.

[0057] Ammonia, as an important chemical raw material and a major component of nitrogen fertilizer, plays a vital role in global industrial and agricultural production, directly impacting the economic viability of the chemical industry and the sustainability of food production.

[0058] Currently, the main method for synthesizing ammonia in industry is the Haber-Bosch process. However, the Haber-Bosch process usually requires operation under high temperature and high pressure, resulting in huge energy consumption and a high dependence on fossil fuels, which leads to problems such as carbon dioxide emissions that cannot be ignored.

[0059] To address the aforementioned issues, a novel green ammonia synthesis method, ENRR, has been developed. ENRR utilizes renewable electricity to directly reduce nitrogen (N2) to ammonia at ambient temperature and pressure, offering significant energy efficiency advantages and environmental friendliness, thus attracting increasingly widespread research and application. However, the practical application of ENRR still faces numerous challenges, the most critical being the selection and design of the catalyst. This is because existing ENRR catalysts generally exhibit low performance, often suffering from low catalytic efficiency and high cost, thus failing to adequately meet the requirements of commercial applications.

[0060] Studies have shown that electrocatalysts prepared by metallizing two or more metallic elements, such as transition metals iron (Fe), cobalt (Co), molybdenum (Mo), and vanadium (V), can improve their catalytic activity and durability through the synergistic effect between the multiple metals. High-entropy alloys (HEAs) are metals composed of five or more metallic elements in equimolar or near-equimolar ratios (each element accounting for 5%–35%). HEAs have attracted widespread attention in the field of electrocatalysis in recent years due to their unique multi-metallic structure and excellent physicochemical properties (e.g., high hardness, corrosion resistance, and wear resistance).

[0061] Based on the above, in a first aspect, embodiments of this application provide a rutile-type high-entropy metal oxide catalyst. The rutile-type high-entropy metal oxide catalyst in this application embodiment includes Fe, Co, titanium (Ti), V, tin (Sn), oxygen (O), and nitrogen (N), and the rutile-type high-entropy metal oxide catalyst has multiple oxygen vacancies (V... O ) and multiple nitrogen vacancies (V N ).

[0062] It should be understood that the aforementioned Ti and Sn elements can together form a rutile crystal structure.

[0063] The chemical formula of the above-mentioned rutile-type high-entropy metal nitrogen oxide catalyst can be FeCoTiVSnON.

[0064] The introduction of nitrogen vacancies, oxygen vacancies, and lattice nitrogen in the embodiments of this application can have a significant impact on the electrocatalytic performance of rutile high-entropy metal oxide catalysts. The number of oxygen vacancies and nitrogen vacancies is not specifically limited here and can be determined according to reaction conditions, etc.

[0065] This application provides a rutile-type high-entropy metal nitride catalyst with numerous oxygen and nitrogen vacancies. When applied to electrocatalytic ammonia synthesis, these vacancies serve as new active sites, enhancing the catalyst's nitrogen adsorption capacity. The presence of these vacancies also leads to local electronic structure changes, forming new electronic states that can regulate the catalyst's conductivity and electron density distribution, thereby influencing the electron transfer process in the electrocatalytic reaction and improving its activity and selectivity. Furthermore, the five transition metals—Fe, Co, Ti, V, and Sn—exhibit a highly mixed entropy state, exhibiting synergistic effects. The size differences between these metal atoms trigger lattice distortion, exposing more active sites and significantly aiding nitrogen activation. In other words, the synergistic effect between multiple metals optimizes nitrogen adsorption and reaction pathways, thereby increasing the ammonia production rate.

[0066] Therefore, the rutile high-entropy metal nitrogen oxide catalyst of this application embodiment exhibits high catalytic efficiency and good catalytic effect in the electrocatalytic reduction of nitrogen to ammonia, thereby resulting in a high yield of ammonia.

[0067] In some embodiments, the average particle size of the rutile high-entropy metal nitride catalyst is 8.44 nm to 8.82 nm.

[0068] For example, the average particle size of rutile high-entropy metal nitride catalysts can be 8.44 nm, 8.53 nm, 8.61 nm, 8.75 nm, 8.80 nm, or 8.82 nm, etc.

[0069] This application provides a rutile-type high-entropy metal nitride catalyst. The average particle size of this rutile-type high-entropy metal nitride catalyst is small, which exposes more active sites and increases its specific surface area. Thus, when the rutile-type high-entropy metal nitride catalyst is applied in an electrocatalytic ammonia synthesis unit, the effective contact area with nitrogen is larger, which is more conducive to the activation of nitrogen. As a result, the rutile-type high-entropy metal nitride catalyst exhibits higher catalytic efficiency and better catalytic effect in the electrocatalytic reduction of nitrogen to ammonia, thereby increasing the yield of ammonia.

[0070] In some embodiments, the atomic ratio of Fe, Co, Ti, V, Sn, O and N elements in the rutile high-entropy metal oxide catalyst, based on a total atomic weight of 100 at.%, can be 4.56:3.90:8.67:7.92:8.26:60.63:6.06.

[0071] This application provides a rutile-type high-entropy metal nitride catalyst. On one hand, although the atomic weights of the various elements are not entirely identical, the error is only between 5 at.% and 35 at.%, indicating that the catalyst belongs to the high-entropy metal nitride category. On the other hand, the sum of the atomic weights of O and N elements is more than twice the sum of the atomic weights of other metal elements, indirectly confirming that the catalyst belongs to the rutile-type metal nitride category. Therefore, the catalyst of this application embodiment belongs to the rutile-type high-entropy metal nitride catalyst category.

[0072] In some embodiments, the rutile high-entropy metal oxide catalyst is a single-phase rutile high-entropy metal oxide catalyst.

[0073] It should be understood that rutile-type high-entropy metal nitrogen oxide catalysts have a single-phase rutile crystal structure.

[0074] This application provides a rutile-type high-entropy metal nitride catalyst. The rutile-type high-entropy metal nitride catalyst has significantly different atomic radii and exhibits lattice distortion, resulting in irregular and distorted unit cells. This exposes more active sites, increasing its specific surface area. Therefore, when applied to an electrocatalytic ammonia synthesis unit, the rutile-type high-entropy metal nitride catalyst has a larger effective contact area with nitrogen, which is more conducive to nitrogen activation. Consequently, the rutile-type high-entropy metal nitride catalyst exhibits higher catalytic efficiency and better catalytic effect in the electrocatalytic reduction of nitrogen to ammonia, leading to a higher ammonia yield.

[0075] Secondly, embodiments of this application provide an electrocatalytic ammonia synthesis apparatus, which includes the aforementioned rutile-type high-entropy metal nitrogen oxide catalyst.

[0076] This application provides an electrocatalytic ammonia synthesis device, which uses rutile high-entropy metal nitrogen oxides as a catalyst to electrocatalyze the reduction of nitrogen to ammonia. Since rutile high-entropy metal nitrogen oxide catalysts can provide a high ammonia production rate and exhibit excellent selectivity for ammonia synthesis in the ENRR reaction, they have high Faraday efficiency, which is beneficial for industrial production and application.

[0077] Thirdly, embodiments of this application provide a method for preparing a rutile-type high-entropy metal oxide catalyst. (See reference...) Figure 1 As shown, the preparation process of this rutile high-entropy metal oxide catalyst may include the following steps:

[0078] S01. Forms rutile-type high-entropy metal oxides containing Fe, Co, Ti, V, Sn, and O elements.

[0079] The chemical formula of the above-mentioned rutile-type high-entropy metal oxide can be FeCoTiVSnO.

[0080] S02. Rutile high-entropy metal oxides are subjected to plasma nitriding treatment to form rutile high-entropy metal oxide catalysts.

[0081] Among them, rutile high-entropy metal nitride catalysts include Fe, Co, Ti, V, Sn, O and N elements, and rutile high-entropy metal nitride catalysts have multiple oxygen vacancies and multiple nitrogen vacancies.

[0082] This application provides a method for preparing a rutile-type high-entropy metal oxide catalyst. First, a rutile-type high-entropy metal oxide containing five transition metal elements (Fe, Co, Ti, V, and Sn) is prepared. Then, the rutile-type high-entropy metal oxide is subjected to plasma nitriding treatment to obtain a rutile-type high-entropy metal oxide catalyst with multiple active sites. The raw materials for preparing this rutile-type high-entropy metal oxide catalyst are abundant and inexpensive, thus offering high cost-effectiveness. Furthermore, the preparation method is simple and novel, meets the requirements of green chemistry, and is conducive to continuous production and large-scale rapid mass production.

[0083] [Step S01]

[0084] The above step S01 can be as follows: Figure 2 As shown, the specific steps include the following:

[0085] S011. SnCl2, CoCl2·6H2O, FeCl3·6H2O, Ti(OC4H9)4 and NH4VO3 are all dispersed in a solvent in equal molar masses to form a solution.

[0086] In practical applications, the solvents mentioned above can be ethylene glycol, etc.

[0087] The molar masses of SnCl2, CoCl2·6H2O, FeCl3·6H2O, Ti(OC4H9)4, and NH4VO3 can all be 0.265 mmol, 0.465 mmol, 0.665 mmol, or 1 mmol, etc. Limiting the molar masses of SnCl2, CoCl2·6H2O, FeCl3·6H2O, Ti(OC4H9)4, and NH4VO3 is to ensure that the percentage error of various metal elements in the rutile high-entropy metal nitride catalyst is within 5% to 35%, resulting in a more uniform metal distribution and thus forming a high-entropy metal nitride.

[0088] S012. Add alkali to the solution and adjust the pH to neutral, then let it stand at the first temperature to obtain a solid powder.

[0089] If the first temperature is too low, it will be difficult to form the desired product; if the first temperature is too high, the power consumption will be too high. Therefore, the first temperature is set to 180℃~250℃, which is a relatively high temperature that allows the components to mix evenly. For example, the first temperature can be 180℃, 190℃, 200℃, 210℃, 220℃, 240℃, or 250℃, etc.

[0090] In practical applications, the above-mentioned alkaline solution can be sodium hydroxide (NaOH) solution, etc.

[0091] S013. The solid powder is calcined at a second temperature and then cooled to form a rutile-type high-entropy metal oxide.

[0092] If the second temperature is too high, unwanted impurities may precipitate, affecting the rutile high-entropy metal nitride catalyst. Conversely, if the temperature is too low, crystal formation will be impossible. Therefore, the second temperature is set to 550℃–650℃ to ensure the formation of a single-crystal rutile high-entropy metal nitride catalyst. For example, the second temperature can be 550℃, 580℃, 600℃, 610℃, 620℃, 640℃, or 650℃.

[0093] As an example, step S011 can be as follows: Figure 3 As shown, specifically:

[0094] S0111. Disperse 0.465 mmol of SnCl2, CoCl2·6H2O, FeCl3·6H2O, Ti(OC4H9)4 and NH4VO3 in 40 mL to 60 mL of ethylene glycol and stir continuously until a homogeneous solution is formed.

[0095] Ethylene glycol is a solvent that can disperse various solid metals and form a homogeneous solution. Ethylene glycol has a boiling point of 197.3℃, close to 200℃, which allows the temperature after the subsequent addition of alkali solution to reach approximately 200℃.

[0096] S0112. Continuously stir the solution and add 2 mL to 6 mL of 0.5 M to 1.5 M NaOH solution to adjust the pH to 7. Then transfer it to a 100 mL high-pressure reactor and let it stand at 180 °C to 250 °C for 10 h to 14 h. Wash the obtained product several times with ethanol and water respectively and then dry it to obtain a solid powder.

[0097] It should be understood that adding NaOH solution to a solution creates an alkaline environment, allowing SnCl2, CoCl2·6H2O, and FeCl3·6H2O to react with the NaOH and neutralize the solution, forming hydroxides. It should be noted that if multiple parts of NaOH solution are added, the product of their volumes and concentrations must be the same to ensure a pH of 7.

[0098] The aforementioned high-pressure reactor can rotate, which makes the solution react more uniformly at 200°C.

[0099] S0113. The solid powder is placed in an air atmosphere in a tube furnace and calcined at 550℃~650℃ for 1h~4h, and then naturally cooled to room temperature to obtain rutile-type high-entropy metal oxide.

[0100] Therefore, rutile-type high-entropy metal oxides (FeCoTiVSnO) containing five transition metal elements—Fe, Co, Ti, V, and Sn—can be prepared by hydrothermal method.

[0101] [Step S02]

[0102] The above step S02 can be as follows: Figure 4 As shown, the specific steps include the following:

[0103] S021. Rutile high-entropy metal oxide is placed in the cavity of a nitrogen-rich discharge plasma device, and nitrided for 1h to 4h by applying a voltage of 45kV to 70kV to form a rutile high-entropy metal oxide catalyst.

[0104] It should be understood that when rutile high-entropy metal oxides are placed in the cavity of a nitrogen-rich discharge plasma device with two electrodes, a glow discharge effect occurs when a certain high voltage is applied to the two electrodes. The generated nitrogen plasma bombards the surface of the rutile high-entropy metal oxides, nitriding them to obtain rutile high-entropy metal nitrides.

[0105] Furthermore, the voltage was chosen to be 50kV. In the cavity of the nitrogen-rich discharge plasma device, the nitrogen near the positive and negative electrodes of the plasma device is transformed into plasma, which continuously bombards the surface of the rutile high-entropy metal oxide to form oxygen vacancies and nitrogen vacancies. At the same time, due to plasma nitriding, the surface of the rutile high-entropy metal oxide is directly attacked at high temperature, resulting in a large number of vacancies on its surface.

[0106] Furthermore, a processing time of 2 hours was selected to ensure the formation of a large number of oxygen and nitrogen vacancies.

[0107] This application provides a method for preparing a rutile-type high-entropy metal oxide catalyst. First, a rutile-type high-entropy metal oxide containing five transition metal elements (Fe, Co, Ti, V, and Sn) is prepared using a hydrothermal method. Then, the prepared rutile-type high-entropy metal oxide is treated with a plasma nitriding process to obtain a rutile-type high-entropy metal oxide with multiple active sites. This rutile-type high-entropy metal oxide, due to the introduction of oxygen and nitrogen vacancies during preparation, facilitates nitrogen adsorption and provides additional active sites. Simultaneously, the five transition metal elements are in a highly mixed entropy state, with synergistic effects among the metals. Furthermore, the lattice distortion effect caused by the differences in atomic size among the metals exposes more active sites, resulting in a catalyst exhibiting remarkable catalytic performance in the electrocatalytic reduction of nitrogen to ammonia. Moreover, the raw materials for this catalyst are abundant and inexpensive, thus offering higher cost-effectiveness. The preparation method is simple and novel, conforms to the principles of green chemistry, and is conducive to continuous production and large-scale rapid mass production.

[0108] The following examples illustrate the preparation methods and applications of the rutile-type high-entropy metal nitride catalysts provided in this application and the rutile-type titanium nitride catalysts provided in the comparative examples.

[0109] I. Examples of the rutile-type high-entropy metal nitride catalyst and its preparation method of this application:

[0110] Example 1

[0111] The steps are as follows:

[0112] (1). Disperse 0.465 mmol of SnCl2, CoCl2·6H2O, FeCl3·6H2O, Ti(OC4H9)4 and NH4VO3 in 50 mL of ethylene glycol and stir continuously until a solution is formed.

[0113] (2) Continue stirring the solution and add 3 mL of 1M NaOH solution to adjust the pH to 7.

[0114] (3) The pH-adjusted solution was transferred into a 100 mL high-pressure reactor, allowed to stand at 200 °C for 12 h, and then washed three times with ethanol and water respectively before drying to obtain a solid powder.

[0115] (4) The solid powder was placed in a tube furnace with an air atmosphere and calcined at 600°C for 2 hours. It was then naturally cooled to room temperature to obtain FeCoTiVSnO.

[0116] (5). FeCoTiVSnO was placed in the cavity of a nitrogen-rich discharge plasma device, a voltage of 50kV was applied, and after treatment for 2h, FeCoTiVSnON was obtained.

[0117] In FeCoTiVSnON, based on a total atomic weight of 100 at.%, the atomic weight ratios of Fe, Co, Ti, V, Sn, O, and N are 4.56:3.90:8.67:7.92:8.26:60.63:6.06.

[0118] Example 2

[0119] The steps are as follows:

[0120] (1). Disperse 0.265 mmol of SnCl2, CoCl2·6H2O, FeCl3·6H2O, Ti(OC4H9)4 and NH4VO3 in 40 mL of ethylene glycol and stir continuously until a solution is formed.

[0121] (2) Continue stirring the solution and add 6 mL of 0.5 M NaOH solution to adjust the pH to 7.

[0122] (3) The pH-adjusted solution was transferred into a 100 mL high-pressure reactor, allowed to stand at 220 °C for 10 h, and then washed twice with ethanol and water respectively before drying to obtain a solid powder.

[0123] (4) The solid powder was placed in a tube furnace with an air atmosphere and calcined at 580°C for 3 hours. It was then naturally cooled to room temperature to obtain FeCoTiVSnO.

[0124] (5) FeCoTiVSnO was placed in the cavity of a nitrogen-rich discharge plasma device, a voltage of 60kV was applied, and after treatment for 4h, FeCoTiVSnON was obtained.

[0125] In FeCoTiVSnON, based on a total atomic weight of 100 at.%, the atomic weight ratios of Fe, Co, Ti, V, Sn, O, and N are 4.56:3.90:8.67:7.92:8.26:60.63:6.06.

[0126] Example 3

[0127] The steps are as follows:

[0128] (1). Disperse 1 mmol of SnCl2, CoCl2·6H2O, FeCl3·6H2O, Ti(OC4H9)4 and NH4VO3 in 50 mL of ethylene glycol and stir continuously until a solution is formed.

[0129] (2). Continue stirring the solution and add 2 mL of 1.5 M NaOH solution to adjust the pH to 7.

[0130] (3) The pH-adjusted solution was transferred into a 100 mL high-pressure reactor, allowed to stand at 180 °C for 14 h, and then washed four times with ethanol and water respectively before drying to obtain a solid powder.

[0131] (4) The solid powder was placed in a tube furnace with an air atmosphere and calcined at 620°C for 1 hour, and then naturally cooled to room temperature to obtain FeCoTiVSnO.

[0132] (5) FeCoTiVSnO was placed in the cavity of a nitrogen-rich discharge plasma device, a voltage of 70 kV was applied, and after treatment for 3 h, FeCoTiVSnON was obtained.

[0133] In FeCoTiVSnON, based on a total atomic weight of 100 at.%, the atomic weight ratios of Fe, Co, Ti, V, Sn, O, and N are 4.56:3.90:8.67:7.92:8.26:60.63:6.06.

[0134] Comparative Example 1

[0135] The steps are as follows:

[0136] (1). The purchased commercial rutile titanium dioxide (TiO2) powder was placed in the cavity of a nitrogen-rich discharge plasma device, and a voltage of 50 kV was applied. After treatment for 2 hours, rutile titanium nitride catalyst (TiON) was obtained.

[0137] To verify the progressiveness of the embodiments of this application, the samples prepared in Example 1 and Comparative Example 1 are tested below.

[0138] The test methods and conclusions are as follows:

[0139] FeCoTiVSnON and TiON were used as working electrode catalysts to test their ability to electrocatalyze the reduction of nitrogen to ammonia at room temperature.

[0140] The FeCoTiVSnON in Example 1 was prepared using a hydrothermal combined with plasma nitriding process, which has advantages such as safe preparation process, simple operation, and environmental friendliness. The TiON in Comparative Example 1 was prepared by plasma nitriding of commercial rutile TiO2, which also has advantages such as safe preparation process, simple operation, and environmental friendliness.

[0141] The refined X-ray diffraction (XRD) pattern of FeCoTiVSnON in Example 1 is as follows: Figure 5 As shown in curve L1, FeCoTiVSnON has a rutile structure, belonging to the tetragonal crystal system and space group P42 / mnm(136). The diffraction peaks at 27.09°, 35.07°, 53.49°, and 67.47° correspond to the (110), (101), (211), and (301) crystal planes, respectively. Furthermore, Figure 5 No other peaks were observed, indicating that FeCoTiVSnON, besides its rutile crystal structure, did not contain any other crystalline phases and is a single-crystal structure. The refined XRD pattern of TiON in Comparative Example 1 is shown below. Figure 5 As shown in curve L2, TiON is a single-phase rutile crystal structure. Compared with FeCoTiVSnON, the diffraction peaks of TiON are slightly shifted to lower angles, with the shift of the (211) crystal plane diffraction peak being particularly obvious. This also indicates that FeCoTiVSnON has undergone lattice distortion, thus having more active sites.

[0142] It should be noted that, Figure 5 The horizontal axis represents the 2θ angle in degrees, and the vertical axis represents the intensity in au.

[0143] The scanning electron microscope (SEM) image of FeCoTiVSnON in Example 1 is as follows: Figure 6 As shown, the scanning transmission electron microscope (STEM) of FeCoTiVSnON is as follows: Figure 7 As shown, combined with Figure 6 and Figure 7 As can be seen, FeCoTiVSnON is bulky, and STEM analysis revealed that these bulks are composed of small, irregular nanoparticles with an average particle size of 8.63 ± 0.19 nm. The STEM image of TiON in Comparative Example 1 is shown below. Figure 8 As shown, from Figure 8As can be seen, TiON is composed of small, irregular nanoparticles, with an average particle size of 22.11 ± 0.22 nm. This indicates that FeCoTiVSnON has a smaller average particle size, allowing it to expose more active sites.

[0144] It should be noted that, Figure 6 In this context, 1μm represents the length of the scale bar in the figure as 1μm. Figure 7 and Figure 8 The 50nm in the figure represents a scale bar length of 50μm.

[0145] The X-ray photoelectron spectroscopy (XPS) of FeCoTiVSnON in Example 1 is as follows: Figure 9 As shown in curve L4, characteristic peaks of metal oxidation states (e.g., Fe 2p, Co 2p, Ti 2p, V 2p, and Ni 2p) were observed in the fine spectra of Fe 2p, Co 2p, Ti 2p, V 2p, and Ni 2p. 2+ Co 2+ and V 4+ (etc.) demonstrates that the metals in FeCoTiVSnON exist mostly in oxidized states, and that there are electronic interactions between the metal elements and nitrogen and oxygen atoms; simultaneously, based on the fine spectra of O1s and N1s, lattice oxygen (MO) and oxygen vacancies (V) can be observed. O The presence of ) and lattice nitrogen; in addition, such as Figure 9 As shown in curve L3, compared to FeCoTiVSnO, the Sn 2p, Co 2p, and Ti 2p peaks of FeCoTiVSnON obtained after nitriding shift towards lower binding energies, shifting by 0.3 eV, 0.9 eV, and 0.2 eV, respectively. This is because nitrogen (3.04) has a lower electronegativity than oxygen (3.44), and nitrogen atoms have a weaker ability to attract electrons from surrounding transition metal atoms. This results in an increase in the electron density around transition metal atoms in FeCoTiVSnON compared to FeCoTiVSnO, thus shifting its XPS characteristic peaks towards lower binding energies. This also indicates that the preparation of FeCoTiVSnON was relatively successful.

[0146] It should be noted that, Figure 9 The horizontal axis represents the binding energy in eV, and the vertical axis represents the intensity in au.

[0147] as well as, Figure 10 The image shown is the XPS spectrum of Fe. Figure 11 The image shown is the XPS spectrum of Co2p. Figure 12 The image shown is the XPS spectrum of Ti2p. Figure 13 The image shown is the XPS spectrum of V2p. Figure 14The image shown is the XPS spectrum of Sn3d. Figure 15 The image shown is the XPS spectrum of O1s. Figure 16 The image shown is the XPS spectrum of N1s.

[0148] The electron paramagnetic resonance (EPR) of FeCoTiVSnON in Example 1 is as follows: Figure 17 and Figure 18 As shown in curve L5, oxygen vacancies (Vo) in FeCoTiVSnON at g = 2.003 can be clearly observed. O The signal intensity is higher than that of TiON, indicating that there are more oxygen vacancies (V) on the FeCoTiVSnON surface. O ); at the same time, such as Figure 17 As shown in curve L6, FeCoTiVSnON has more unpaired electrons compared to FeCoTiVSnO, indicating that nitrogen vacancies (V0) are introduced into FeCoTiVSnO along with nitrogen doping during the plasma nitriding process. N Therefore, FeCoTiVSnON has more oxygen and nitrogen vacancies on its surface. The EPR of TiON in Comparative Example 1 is as follows: Figure 18 As shown in curve L7, compared to FeCoTiVSnON, TiON has fewer nitrogen vacancies (V0) on its surface. N ).

[0149] It should be noted that, Figure 17 and Figure 18 The horizontal axis represents the g value, and the vertical axis represents the intensity, with the unit being au.

[0150] The ammonia production rate and Faraday efficiency (FE) of FeCoTiVSnON in Example 1 for the electrocatalytic reduction of nitrogen to ammonia in the optimal potential range (-0.48V vs. RHE to -0.52V vs. RHE) are shown in the figure below. Figure 19 As shown, within the potential range of -0.48V vs. RHE to -0.52V vs. RHE, the ammonia production rate exhibits a trend of first increasing and then decreasing, with the highest value at -0.50V vs. RHE, reaching an ammonia production rate of 174.25 μg·h⁻¹. -1 ·mg cat . -1 The corresponding FE is 48.64%. The ammonia production rate and FE of TiON in Comparative Example 1 during the electrocatalytic reduction of nitrogen to ammonia in the optimal potential range (-0.48V vs. RHE to -0.52V vs. RHE) are as follows: Figure 20As shown, within the potential range of -0.48V vs. RHE to -0.52V vs. RHE, the ammonia production rate exhibits a trend of first increasing and then decreasing, with the highest value at -0.50V vs. RHE, where the ammonia production rate is μg·h⁻¹. -1 ·mg cat . -1 The corresponding FE is 26.01%.

[0151] It should be noted that the above -0.48V vs. RHE means that the potential relative to the reversible hydrogen electrode (RHE) is -0.48V. Other values ​​are similar and will not be described in detail here.

[0152] and, Figure 19 and Figure 20 The horizontal axis represents voltage in V vs. RHE, and the vertical axis on the left represents nitrogen yield in μg·h⁻¹. -1 ·mg cat . -1 The right-hand vertical axis represents Faraday efficiency, expressed as a percentage.

[0153] The cycling stability of FeCoTiVSnON in Example 1 at the optimal potential (-0.50V vs. RHE) is as follows: Figure 21 As shown, the ammonia production rate and FE value of FeCoTiVSnON only fluctuated slightly in the 6-cycle experiment without significant decay, indicating that FeCoTiVSnON has good electrochemical stability in the electrocatalytic nitrogen reduction process.

[0154] It should be noted that, Figure 21 The horizontal axis represents the number of cycles, and the vertical axis represents the nitrogen yield, in μg·h⁻¹. -1 ·mg cat . -1 .

[0155] In summary, in Example 1, FeCoTiVSnON and its preparation method first use a hydrothermal method to prepare FeCoTiVSnO containing five transition metal elements: Fe, Co, Ti, V, and Sn. Then, the obtained FeCoTiVSnO is treated with a plasma nitriding process to obtain FeCoTiVSnON with multiple active sites. Furthermore, commercially available rutile TiO2 was subjected to the same plasma nitriding process to obtain TiON as a control sample. Comparison with the control sample confirms that the FeCoTiVSnON preparation method in Example 1 uses abundant and inexpensive raw materials, thus offering higher cost-effectiveness. Moreover, the preparation method is simple and novel, conforming to the principles of green chemistry.

[0156] This section only introduces the content related to the invention point; the rest can be obtained by referring to relevant technologies, and will not be described in detail here.

[0157] The above embodiments merely illustrate several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of this patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.

Claims

1. A rutile-type high-entropy metal oxide catalyst, characterized in that, The rutile-type high-entropy metal nitride catalyst includes Fe, Co, Ti, V, Sn, O, and N elements, and has multiple oxygen vacancies and multiple nitrogen vacancies.

2. The rutile-type high-entropy metal nitrogen oxide catalyst according to claim 1, characterized in that, The average particle size of the rutile-type high-entropy metal nitrogen oxide catalyst is 8.44 nm to 8.82 nm.

3. The rutile-type high-entropy metal nitrogen oxide catalyst according to claim 1 or 2, characterized in that, The rutile high-entropy metal nitrogen oxide catalyst, based on a total atomic weight of 100 at.%, has an atomic weight ratio of Fe, Co, Ti, V, Sn, O, and N of 4.56:3.90:8.67:7.92:8.26:60.63:6.

06.

4. The rutile-type high-entropy metal oxide catalyst according to claim 1 or 2, characterized in that, The rutile-type high-entropy metal nitrogen oxide catalyst has a single-phase rutile crystal structure.

5. An electrocatalytic ammonia synthesis apparatus, characterized in that, Including rutile-type high-entropy metal nitrogen oxide catalysts as described in any one of claims 1 to 4.

6. A method for preparing a rutile-type high-entropy metal oxide catalyst, characterized in that, Includes the following steps: It forms rutile-type high-entropy metal oxides containing Fe, Co, Ti, V, Sn, and O elements; The rutile-type high-entropy metal oxide is subjected to plasma nitriding treatment to form the rutile-type high-entropy metal nitride catalyst; wherein the rutile-type high-entropy metal nitride catalyst further includes nitrogen element, and the rutile-type high-entropy metal nitride catalyst has multiple oxygen vacancies and multiple nitrogen vacancies.

7. The method for preparing the rutile-type high-entropy metal nitride catalyst according to claim 6, characterized in that, The formation of rutile-type high-entropy metal oxides containing iron, cobalt, titanium, vanadium, tin, and oxygen includes: SnCl2, CoCl2·6H2O, FeCl3·6H2O, Ti(OC4H9)4 and NH4VO3 were all dispersed in a solvent at the same molar mass to form a solution; An alkaline solution is added to the solution and the pH is adjusted to neutral. The solution is then allowed to stand at a first temperature to obtain a solid powder. The first temperature is 180°C to 250°C. The solid powder is calcined at a second temperature and then cooled to form the rutile-type high-entropy metal nitride catalyst; wherein the second temperature is 550℃~650℃.

8. The method for preparing the rutile-type high-entropy metal oxide catalyst according to claim 7, characterized in that, The step of adding an alkaline solution to the solution and adjusting the pH to neutral, followed by standing at a first temperature, to obtain a solid powder comprises: Add 2 mL to 6 mL of a 0.5 M to 1.5 M sodium hydroxide solution to the solution to adjust the pH to neutral. Then transfer the solution to a high-pressure reactor and let it stand at 180 °C to 250 °C for 10 h to 14 h. After washing with ethanol and water in sequence, dry the solution to obtain the solid powder.

9. The method for preparing the rutile-type high-entropy metal nitride catalyst according to claim 7, characterized in that, The step of calcining the solid powder at a second temperature and then cooling it to form the rutile-type high-entropy metal oxide catalyst includes: The solid powder is placed in an air atmosphere in a tube furnace and calcined at 550℃~650℃ for 1h~4h, then naturally cooled to room temperature to form the rutile-type high-entropy metal nitride catalyst.

10. The method for preparing the rutile-type high-entropy metal nitride catalyst according to claim 6, characterized in that, The step of subjecting the rutile-type high-entropy metal oxide to plasma nitriding treatment to form the rutile-type high-entropy metal nitride catalyst includes: The rutile high-entropy metal oxide is placed in the cavity of a nitrogen-rich discharge plasma device, and nitrided for 1 to 4 hours by applying a voltage of 45 kV to 70 kV to form the rutile high-entropy metal oxide catalyst.